ANALISIS PENGARUH E-COMMERCE DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI - Hakim Tiro, Muh Ainul Haq; SS, Vietha Devia (Journal of Development Economic and Social Studies, 2022)
This research was conducted to determine the effect of e-commerce and investment on economic growth in Indonesia. This research is a quantitative research with secondary data and time series throughout 2014-2021. E-commerce variables are supported through the value of e-commerce transactions and the number of business units, while specific investments are assessed from the transportation, warehouse and telecommunications sectors. The results of this study indicate a positive and significant relationship between e-commerce and investment on economic growth in Indonesia.